2019
DOI: 10.1177/1129729819852204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic variation of the axillary veins due to intrathoracic pressure changes: A prospective sonographic study

Abstract: Introduction: The ultrasound-guided axillary vein is becoming a compulsory alternative vessel for central venous catheterization and the anatomical position offers several potential advantages over blind, subclavian vein techniques. Objective: To determine the degree of dynamic variation of the axillary vein size measured by ultrasound prior to the induction of general anesthesia and after starting controlled mechanical ventilation. Design: Prospective, observational study. Methods: One hundred ten patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, the primary venipuncture success rate may be clinically related to the increased first-pass success rate of subclavian vein catheterization and may decrease catheterization-related complications. A recent study also suggested that an increase in the axillary vein area during mechanical ventilation may theoretically improve the first-pass success rate of central venous catheterization [12]. Accordingly, this study examined whether the primary venipuncture success rate could be improved by increasing the csSCV.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, the primary venipuncture success rate may be clinically related to the increased first-pass success rate of subclavian vein catheterization and may decrease catheterization-related complications. A recent study also suggested that an increase in the axillary vein area during mechanical ventilation may theoretically improve the first-pass success rate of central venous catheterization [12]. Accordingly, this study examined whether the primary venipuncture success rate could be improved by increasing the csSCV.…”
Section: Discussionmentioning
confidence: 95%
“…For last decades, the use of ultrasonography during vascular procedures has been suggested as a standard method that enhances overall success and reduces procedure-related complications, by professional organizations [ 9 11 ]. Ultrasonographic assessment can be applied before, during, and after central venous cannulation, and provides clinicians with advantages of success, speed, and safety, by visualizing vessel viability, size, and patency, as well as the location of other adjacent anatomically important structures [ 12 , 33 ]. With respect to ultrasound-guided subclavian vein catheterization, although the quality of evidence is generally weak, the use of ultrasound-guidance is recommended in adult patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of positive endexpiratory pressure (PEEP) for successful cannulation of the subclavian vein (SCV) remains inconclusive [ 1 , 2 ]. A higher PEEP may decrease distance from SCV to the parietal pleura consecutively increasing the periprocedural risk of pneumothorax.…”
Section: Introductionmentioning
confidence: 99%